Konstruksi Thirdspace dari Ziarah Lintas Agama di Makam Soekarno - Tamawiwi, Rio Sario; Lattu, Izak Y.M; Tampake, Tony Christian; Suprabowo, Gunawan Y.A (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2024)
Soekarno's grave in Blitar is busy with pilgrims from various religions daily. This place has become a space for interfaith meetings. The Blitar government also annually facilitates interfaith prayer activities, which are held four times a year as a symbol of fostering a spirit of tolerance. When pilgrims hold a prayer ritual, a third space is formed for social interaction between the first room and the second room. This article aims to answer the ontological question regarding understanding the encounter between interfaith pilgrims who form the third space at the Soekarno Tomb. This article uses a qualitative descriptive method through literature review, observations, and in-depth interviews in the Soekarno Grave Area, Blitar. The research results concluded that interfaith encounters during the pilgrimage at Soekarno's grave created a thirdspace construction according to Edward Soja's theory, which can be applied at the individual, institutional and community levels. Based on these findings, the main argument is that Soja's thirdspace construction is a framework for thinking to build social glue. The thirdspace construction allows humans to interact socially, which connects different characters and traits.